Linking the cognitive load induced by route instruction types and building configuration during indoor route guidance, a usability study in VR. Issue 10 (3rd October 2022) - De Cock, Laure; Van de Weghe, Nico; Ooms, Kristien; Saenen, Ignace; Van Kets, Niels; Van Wallendael, Glenn; Lambert, Peter; De Maeyer, Philippe
Abstract: Every route instruction type (e.g. map, symbol, photo) induces a specific cognitive load. However, when these types are used at different decision points in a building, the building configuration of these points also influences the induced cognitive load. Therefore, the process of route guidance results in an interaction between the instruction type and the decision point, which determines the induced cognitive load. One way of reducing cognitive load during route guidance is by using adaptive systems that show specific route instruction types at specific decision points. Therefore, in this VR experiment, the usability of such an adaptive indoor route guidance system is tested by tracking the wayfinding and gaze behavior of the users. First, the difference in wayfinding and gaze behavior between all route instruction types is compared. Next, the building configuration at the decision points is quantified through the architectural theory of space syntax, and the correlation with the wayfinding and gaze behavior is determined. Our findings indicate that adapting the route instruction type does make a difference for the user.